An in-vitro study on corn-shaped balloon-enhanced thrombolysis. Issue 2 (April 2014) - Yan, Shiju; Song, Chengli
Abstract: Background : Glossy balloons were used to enhance deep vein thrombolysis. However, thrombi tend to yield in the balloon dilatation due to their smooth surface. It may be preferable to enhance thrombolysis by using balloons with a rough surface, instead of balloons with a smooth surface.Material and methods : Four rabbits were used for the experiment and 60 blood clot samples were obtained, and the samples were randomly separated into one control group and four balloon-solubilised groups. Urokinase solution (5000 U/ml) was used as the thrombolytic drug. The balloon-solubilised groups were enhanced respectively by 1 atm and 2 atm pressurised glossy balloons, and 1 atm and 2 atm pressurised corn-shaped balloons. Thrombolysis rates and residual rates for different granularities of blood clots were calculated for comparasion.Results : Thrombolysis rates of the groups using corn-shaped balloons were higher than those of the groups using glossy balloons ( p = 0.003 and p = 0.002). Residual rates of Φ ≥ 3.7 mm blood clots for the groups using corn-shaped balloons were lower than those for the groups using glossy balloons ( p < 0.001 and p < 0.001).Conclusion : Balloons could be used to enhance thrombolysis; under the same balloon dilatation pressure, thrombolysis rates when using corn-shaped balloons are better than those when using glossy balloons.